High Field NMR Investigation of Yb2Pt2O7 - Takahashi, Sean (My University, 2017)
The rare-earth pyrochlore oxides are the prime example of three-dimensional frustrated magnetism. Pyrochlores are of the chemical form A2B2O7 where the A site is a rare-earth metal and B is a non-magnetic ion. The A and B sites separately form a network of corner-sharing tetrahedra which are interwoven with each other. The geometric frustration of the pyrochlores make them extremely interesting as it introduces new and complicated behaviour that has not been studied before. It is typically difficult to conduct NMR experiments on such materials as many of the more well studied pyrochlore materials do not have appropriate nuclei for NMR. Yb2Pt2O7 is an exception as platinum is an excellent atom for NMR experiments. Yb2Pt2O7 is an effective S=1/2 XY pyrochlore, meaning that the magnetic moment on the Yb ion is anisotropic. 195Pt high field NMR measurements were performed on a powder sample of the pyrochlore Yb2Pt2O7 in fields from 1T to 8T. The NMR frequency shift increased rapidly at low temperature until it was saturated due to the magnetic field strength. The spin-lattice relaxation rate, 1/T1, showed exponential behaviour from ~20K down to 1.8K for the higher fields of 2T, 4T and 8T. The rapid decrease in 1/T1 indicates that the spin fluctuations freeze out at temperatures well before the known zero-field transition to a ferromagnetic state at ~0.3mK. The 1/T1 data was fit to an exponential e^(-∆/T) to extract an energy scale ∆. Finding the peak of the 1/T1T as a function of temperature and scaling analysis were also used to determine an energy scale. All three methods showed the same behaviour with magnetic field strength, where ∆ decreases linearly as the field strength is lowered. Low field NMR experiments are being planned to determine if this behaviour continues below 1T.